Efeito imunomodulador do Limosilactobacillus fermentum (LF61) e Lacticaseibacillus paracasei (LPc-G110) em modelo murino da Síndrome da Asma e Rinite Alérgicas Combinadas (CARAS) - Cavalcanti, Raquel Fragoso Pereira (2023)
Combined allergic asthma and rhinitis syndrome (CARAS) is an allergic inflammatory disease of the airways orchestrated by the type 2 immune response. The airways and the intestine are considered interfaces in which there is close interaction. The intestine houses an extensive microbial community, known as microbiota, which exerts influence not only in situ, but also on other systems, such as the respiratory system. Specific mechanisms of communication between interfaces, via the gut-lung axis, have been the subject of intense investigation, however, the effect of gut-modulating functional agents, such as probiotics, on allergic airway disorders has not been fully elucidated. Therefore, the objective of this study was to evaluate the effect of supplementation with Limosilactobacillus fermentum (LF61) or Lacticaseibacillus paracasei (LPc-G110) in animals with CARAS. BALB/c mice (n = 5) were distributed into Basal, L. fermentum (LF61), L. paracasei (LPc-G110), Allergic (CARAS), supplemented with LF61 and Allergic (LF61/CARAS), supplemented with LPc groups. -G110 and allergic (LPc-G110/CARAS) and allergic treated with dexamethasone (Dexa). The experimental protocols were approved by CEUA/UFPB (7316150420). BALB/c mice were sensitized and challenged with ovalbumin (OVA) after being supplemented with 1x109 CFU of LF61 or LPc-G110. Animals with CARAS and previously supplemented with probiotics showed a decrease (p<0.05) in the migration of inflammatory cells, mainly eosinophils, to the nasal (NALF) and bronchoalveolar (BALF) fluids, as well as a reduction in clinical signs of rhinitis, such as sneezing, nasal rubbing, and histamine-induced nasal hyperreactivity compared to animals with CARAS. In the systemic context, LF61 and LPc-G110 reduced eosinophilia and serum levels of OVA-specific IgE. The altered histological aspects in the nasal and lung tissues of animals with CARAS were significantly improved by LF61 and LPc-G110. In BALF, the immunomodulatory effect was revealed by the decrease in type 2 and 3 cytokines (IL-4, IL-13, IL-5 and IL-17A) correlated with the increase in type 1 (IFN-γ) and Treg (IL -10). In addition, positive modulation of the transduction factor FOXP3 and negative modulation of MAPKs (p-p38 and p-ERK1/2) were evidenced. These effects correlate with the amplification of the intestinal response, via increased levels of short-chain fatty acids (SCFAs), and maintenance of the barrier function of the intestinal epithelium through the increase in occlusion junctions (ZO-1), corroborating the integrity of the intestinal colon tissue. Therefore, the results of this study demonstrate, in an unprecedented way, that LF61 and LPc-G110, administered orally, negatively modulate the type 2 immune response observed in CARAS, activation of intracellular transduction factor that induces the production of the regulatory molecule IL-10 and increased short-chain fatty acids (butyrate, propionate and acetate).